2015
DOI: 10.1021/jacs.5b02653
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessing and Recycling of Highly Cross-Linked Ion-Conducting Networks through Transalkylation Exchanges of C–N Bonds

Abstract: Exploiting exchangeable covalent bonds as dynamic cross-links recently afforded a new class of polymer materials coined as vitrimers. These permanent networks are insoluble and infusible, but the network topology can be reshuffled at high temperatures, thus enabling glasslike plastic deformation and reprocessing without depolymerization. We disclose herein the development of functional and high-value ion-conducting vitrimers that take inspiration from poly(ionic liquid)s. Tunable networks with high ionic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
413
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 438 publications
(427 citation statements)
references
References 32 publications
14
413
0
Order By: Relevance
“…28 Such polyionic networks were synthesized via a one-pot process through a polyaddition of α-azide-ω-alkyne monomers involving a thermal ‘non-click’ azide-alkyne Huisgen 1,3-dipolar cycloaddition and a simultaneous cross-linking step, using a bifunctional alkylating agent such as dibromo and diiodo alkanes or alkyl mesylates (Fig. 6).…”
Section: Vitrimer Materialsmentioning
confidence: 99%
“…28 Such polyionic networks were synthesized via a one-pot process through a polyaddition of α-azide-ω-alkyne monomers involving a thermal ‘non-click’ azide-alkyne Huisgen 1,3-dipolar cycloaddition and a simultaneous cross-linking step, using a bifunctional alkylating agent such as dibromo and diiodo alkanes or alkyl mesylates (Fig. 6).…”
Section: Vitrimer Materialsmentioning
confidence: 99%
“…17). 107 The ratio between alkylating groups (bromide, iodide or mesyl) and azide (or alkyne or 1,2,3-triazole) group was maintained equal Although, quantitative N-alkylation/cross-linking is physically unattainable, these ion conducting networks contain significantly more cross-linked units compared to conventional networks where high M n with the presence of entanglements and a few percent of covalent cross-links are sufficient to afford well cross-linked materials having few extractibles and low swelling in good solvents of the initial polymer. For TPIL networks, the dangling chains and elastically-active cross-links afford ionically chartged units.…”
Section: Monotopic Synthesis Of Recyclable and Reprocessable Highly Cmentioning
confidence: 99%
“…Currently, as recently reviewed by our group9, only a limited number of associative exchange chemistries101112131415161718192021222324 have been explored in the context of vitrimers, and one of the main challenges is the precise control of the exchange kinetics. Although Leibler and co-workers demonstrated that epoxy-based transesterification vitrimers can be controlled by changing catalysts8, the exchange reaction remains slow and high catalyst loadings and temperatures are required to enable processing in a reasonable timeframe678.…”
mentioning
confidence: 99%